2016
DOI: 10.1021/acs.chemrestox.6b00306
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenesis of the Oral Cavity: Environmental Causes and Potential Prevention by Black Raspberry

Abstract: Worldwide, cancers of the oral cavity and pharynx comprise the sixth most common malignancies. Histologically, more than 90% of oral cancers are squamous cell carcinoma (SCC). Epidemiologic data strongly support the role of exogenous factors such as tobacco, alcohol, and human papilloma virus infection as major causative agents. Avoidance of risk factors has only been partially successful, and survival rates have not improved despite advances in therapeutic approaches. Therefore, new or improved approaches to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
86
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(97 citation statements)
references
References 169 publications
6
86
0
5
Order By: Relevance
“…However, as a novel and promising model, there are still several barriers to the full application of GEMMs. Firstly, although the introduction of mice expressing Cre recombinase is driven by oral mucosa-specific promoters such as K5 or K14, the tumors generated by GEMMs have low specificity and appear in sites other than the oral cavity, such as the skin, tongue, esophagus, and forestomach (180,181,185,186). Secondly, because of the full range of genetic changes caused by gene editing, GEMMs have a short lifespan and a high mortality rate, and highly malignant OSCC may not develop.…”
Section: Characteristics Of Gemmsmentioning
confidence: 99%
“…However, as a novel and promising model, there are still several barriers to the full application of GEMMs. Firstly, although the introduction of mice expressing Cre recombinase is driven by oral mucosa-specific promoters such as K5 or K14, the tumors generated by GEMMs have low specificity and appear in sites other than the oral cavity, such as the skin, tongue, esophagus, and forestomach (180,181,185,186). Secondly, because of the full range of genetic changes caused by gene editing, GEMMs have a short lifespan and a high mortality rate, and highly malignant OSCC may not develop.…”
Section: Characteristics Of Gemmsmentioning
confidence: 99%
“…Head and neck squamous cell carcinoma (HNSCC), the vast majority of which occurs in the oral cavity, is the sixth most common malignancy worldwide, representing a major international health problem (1). HNSCC is the most traumatic form of malignancy due to its visible distortion of the face, and disruption of breathing, speaking and swallowing (2).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological data strongly support the role of exogenous factors such as tobacco, alcohol and human papilloma virus infection as causative factors; other factors (betel quid chewing, smokeless tobacco, marijuana, and certain dietary components) have also been implicated in the development of HNSCC (1). A recent study found that alcohol consumption combined with tobacco smoking results in a supra-multiplicative synergistic effect which enhances cancer risk up to 14-fold (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The carcinoma of the tonsil represents 10-15% of total malignant tumors in the oral cavity, have a predilection for male (4:1 is the male: female ratio) especially between the 6 th -8 th decade of life and the great majority is represented by squamous cell carcinomas [1,4]. These patients often present a history of alcohol and tobacco abuse, human papilloma virus [5][6][7][8]. Due to the lack of symptoms in the early stages of the disease the patients report to medical examination late, in advanced stages, when the prognosis is poor despite multimodal oncologic treatment (surgery, radiotherapy, chemotherapy).…”
mentioning
confidence: 99%